Pengaruh Waktu Tunggu terhadap Wait Satisfaction Pasien di Instalasi Rawat Jalan RSAL dr. Ramelan - Dewanto, Aryo; Herjunianto (Jurnal Aplikasi Manajemen, 2014)
The objective of this paper is to analyze the influence of wait time against wait satisfaction at outpatient unit of dr. Ramelan Navy Hospital. Thestudy is a cross sectional explanatory research which respondent were randomly selected at Endrocrinology, Cardiology and Neurology clinics on May 2014. Expected Waiting Time (EWT), Perceived Waiting Time (PWT) and Disconfirmation were measured by questioner, while Actual Waiting Time (AWT) measured by observation. Wait satisfaction as dependent variable were measured by two questions. The wait satisfaction values was related to four different independent variables using simple linear regression. The results shows that PWT, AWT, Disconfirmation significantly influence wait satisfaction, while EWT did not. Disconfirmation had the greatest role in influencing wait satisfaction.